Characteristics of global retractions of schizophrenia-related publications: A bibliometric analysis - Chen, Pan; Li, Xiao-Hong; Su, Zhaohui; Tang, Yi-Lang; Ma, Yi; Ng, Chee H.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2022)
Objectives: The growing rate of retraction of scientific publications has attracted much attention within the academic community, but there is little knowledge about the nature of such retractions in schizophrenia-related research. This study aimed to analyze the characteristics of retractions of schizophrenia-related publications. Methods: The Web of Science was searched for eligible studies. A bibliometric analysis was conducted to describe the characteristics of the retractions using R software and Excel 2019. Content analysis was conducted to examine the essential components of retraction notices. Results: A total of 36 retracted publications with 415 citations were identified from 1997 to 2021, of which, 83.3% occurred in the last decade. The overall retraction rate was 0.19%, with most of them (29; 80.56%) from the United Kingdom. The retractions were published in 33 journals, and the 2020 IFs ranged between 0.17 and 49.96 (Median=3.93). The retractions involved 21 research areas, particularly in Psychiatry (19; 52.78%), Neurosciences Neurology (10; 27.78%), and Psychology (7; 19.44%). Data issues (17; 42.22%), administrative errors of the publishers (5; 13.89%), and study design (4; 11.11%) were the top three reasons for retractions. Conclusions: This study provides an insight into retractions of schizophrenia-related publications. Institutional governance should be further strengthened to improve the scrutiny of publications, prevent continued citation and erroneous propagation after retraction.